Ionoskins: Nonvolatile, Highly Transparent, Ultrastretchable Ionic Sensory Platforms for Wearable Electronics. (20th November 2019) - Kim, Yong Min; Moon, Hong Chul
Abstract: The primary technology of next‐generation wearable electronics pursues the development of highly deformable and stable systems. Here, nonvolatile, highly transparent, and ultrastretchable ionic conductors based on polymeric gelators [poly(methyl methacrylate‐ ran ‐butyl acrylate), PMMA‐ r ‐PBA] and ionic liquids (IL) are proposed. A crucial strategy in the molecular design of polymer gelators is copolymerization of PMMA and IL‐insoluble low glass transition temperature ( T g ) polymers that can be deformed and effectively dissipate applied strains. Highly stretchable (elongation limit ≈850%), mechanically robust (elastic modulus ≈3.1 × 10 5 Pa), and deformation durable (recovery ratio ≈96.1% after 500 stretching/releasing cycles) gels are obtained by judiciously adjusting the molecular characteristics of polymer gelators and gel composition. An extremely simple "ionic" strain sensory platform is fabricated by directly connecting the stretchable gel and a digital multimeter, exhibiting high sensitivity (gauge factor ≈2.73), stable operation (>13 000 cycles), and nonvolatility (>10 d in air). Moreover, the skin‐type strain sensor, referred to as ionoskin, is demonstrated. The gels are attached to a part of the body (e.g., finger, elbow, knee, or ankle) and various human movements are successfully monitored. The ionoskin renders the opportunity to achieve wearable ubiquitous electronics such as healthcare devices and smart textile systems. Abstract : An ultrastretchable, highly transparent, and mechanically durable ionic strain sensory platform is proposed based on poly(methyl methacrylate‐ ran ‐butyl acrylate) random copolymer gelators. The gel‐based strain sensors, referred to as ionoskin, exhibit a large deformation limit, high sensitivity, nonvolatility, and operational stability, by which various motions of the finger, elbow, knee, and ankle are successfully monitored.